2018
DOI: 10.1111/tpj.13786
|View full text |Cite
|
Sign up to set email alerts
|

Sequential gene activation and gene imprinting during early embryo development in maize

Abstract: Gene imprinting is a widely observed epigenetic phenomenon in maize endosperm; however, whether it also occurs in the maize embryo remains controversial. Here, we used high-throughput RNA sequencing on laser capture microdissected and manually dissected maize embryos from reciprocal crosses between inbred lines B73 and Mo17 at six time points (3-13 days after pollination, DAP) to analyze allelic gene expression patterns. Co-expression analysis revealed sequential gene activation during maize embryo development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
(127 reference statements)
2
25
0
Order By: Relevance
“…In plants, imprinting primarily occurs in the endosperm; however, recent studies have shown that a portion of genes are also imprinted in the embryo of Arabidopsis thaliana (Raissig et al, 2013), rice (Oryza sativa) (Luo et al, 2011), and maize (Zea mays) (Meng et al, 2017). This uniparental transcription pattern indicates that, to some extent, parental genomes might not contribute equally to the filial genome, at least for some specific loci, if not at the genome-wide level (Vielle-Calzada et al, 2000;Grimanelli et al, 2005;Autran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, imprinting primarily occurs in the endosperm; however, recent studies have shown that a portion of genes are also imprinted in the embryo of Arabidopsis thaliana (Raissig et al, 2013), rice (Oryza sativa) (Luo et al, 2011), and maize (Zea mays) (Meng et al, 2017). This uniparental transcription pattern indicates that, to some extent, parental genomes might not contribute equally to the filial genome, at least for some specific loci, if not at the genome-wide level (Vielle-Calzada et al, 2000;Grimanelli et al, 2005;Autran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, endosperms carrying two doses of pdx2-mu1023708 are consistently above the threshold for functional vitamin deficiency. While preferential expression of the maternally transmitted pdx2 allele in the embryo due to imprinting could also explain these results, Pdx2 is not among the relatively small set of imprinted genes so far detected in the maize embryo (Meng et al, 2018). Conversely, a dependence of the embryo phenotype on dosage of pdx2 alleles in endosperm would suggest that pyridoxine in endosperm is not only required for endosperm formation, but also for embryo development.…”
Section: Leveraging Allelic Series For Genetic Manipulation Of Vitamimentioning
confidence: 87%
“…As in other flowering plants, seed development in maize is governed by specific temporal and spatial genetic programs, distinguishing early development, filling and maturation on one hand and embryo, endosperm and pericarp on the other Downs et al, 2013;Li et al, 2014;Lu et al, 2013;Meng et al, 2018;Qu et al, 2016). Recently a transcriptome analysis on nucellus (including the fertilized embryo sac) increased the temporal resolution and allowed unprecedented access to information regarding the genetic control of early seed developmental (Yi et al, 2019).…”
Section: Transcriptomes At Embryo/endosperm Interfacesmentioning
confidence: 99%
“…Genome-wide gene expression studies at numerous developmental stages of whole kernels and/or hand-dissected endosperm and embryo Downs et al, 2013;Li et al, 2014;Lu et al, 2013;Meng et al, 2018;Qu et al, 2016) have been complemented by a recent transcriptomic analysis of laser-capture micro-dissected cell types and subcompartments of 8 DAP kernels (Zhan et al, 2015). However, even the latter study did not address specifically the transcriptomic profiles of the embryo/endosperm interfaces and did not answer the question of whether the endosperm at the scutellum/endosperm interface is composed of cells with specific transcriptional identities.…”
Section: Introductionmentioning
confidence: 99%